A critical review on damage modeling and failure analysis of pin joints in fiber reinforced composite laminates. (27th April 2022) - Gupta, Akash; Singh, Manjeet; Singh, Jaswinder; Singh, Sunpreet; Prakash, Chander
Fiber-reinforced composite material plays a vital role in structural engineering due to its lightweight and high strength ratio which becomes a key material in a mechanically fastened pin joint. Recent review articles in this area were restricted to the numerical and experimental approaches which are used for strength prediction of pin joints in polymer matrix composites. The present study begins with an extensive analysis of relevant studies in the provided structurally clamped joint region using numerous numerical approaches and theories of failure. Numerous experimental and numerical approaches are available nowadays and have been cited by the researchers in their respective research to foretell the damage initiation and failure mode in the composite joint. The study gives the review of different numerical analyses of composite joints by utilizing interactive criteria for failure analysis, viz. Tsai-Wu, Tsai-Hill, Yamada Sun's theory predicts failure using higher-order polynomial equations that comprise all stress or strain components, whereas limit stress criteria i.e. Maximum stress criterion which uses linear equations for finding the solution. Progressive Damage Analysis (PDA) quantifies matrix and fiber failure using the material depletion rule preceded by Hashin's theory which offers a good interpretation irrespective of the types of composite material. In the end, various parameters are discussed which enhance joint performance under different loading conditions.